2016
DOI: 10.1097/meg.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate seroprotection against hepatitis B virus and one detected case of hepatitis C virus infection among patients with inflammatory bowel disease

Abstract: A mandatory HBV vaccination significantly increased the number of patients effectively protected against HBV; however, a remarkable number of vaccinated IBD patients had inadequate HBV seroprotection. All IBD patients should be screened for HBV and HCV infections and monitored for anti-HBs titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Among our vaccinated patients, 5/176 (2.8%) were infected by HBV, a finding consistent with data from Poland [ 17 ]. Possible explanation may include an HBsAb titre loss due to immunosuppressive therapies, a not perfectly performed vaccination or a not fully responsive immune system.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among our vaccinated patients, 5/176 (2.8%) were infected by HBV, a finding consistent with data from Poland [ 17 ]. Possible explanation may include an HBsAb titre loss due to immunosuppressive therapies, a not perfectly performed vaccination or a not fully responsive immune system.…”
Section: Discussionsupporting
confidence: 91%
“…From our data, it appears that the risk of HBV infection increases with age; however, this result is surely influenced by the mandatory HBV vaccination. Another important issue is the relationship between IBD and HBsAb status in vaccinated IBD patients; we confirm the finding of Waszczuk et al [ 17 ] who reported a seroprotection rate of 54%, underlining that our patients were vaccinated long before the diagnosis of IBD was made. This confirms our previous finding in a much smaller cohort [ 26 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After reviewing the full texts, 21 studies were included for the analysis 7,17–36 . Details of excluded studies are provided in Table S2 37–51 . Of the included studies, 17 were full articles 7,17–26,29,31–35 and 4 were published as abstracts 27,28,29,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, results of two Greek studies also reported prevalence of 2.3%-5% among IBD patients, which was in accordance to what was expected[ 30 , 31 ]. In addition, a study from Poland, a country with intermediate endemicity, also showed that the prevalence of HBV infection among IBD patients was comparable to that of the general population[ 32 ]. The most recent study by Losurdo et al [ 33 ], published in 2020, evaluated the burden of viral hepatitis in IBD and demonstrated that HCV was more frequent than HBV infection in IBD patients but with low overall prevalence.…”
Section: Hbv Prevalence In Patients With Ibdmentioning
confidence: 99%